Management of Spinal Bone Metastases With Radiofrequency Ablation, Vertebral Reinforcement and Transpedicular Fixation: A Retrospective Single-Center Case Series - Giammalva, Giuseppe Roberto; Costanzo, Roberta; Paolini, Federica; Benigno, Umberto Emanuele; Porzio, Massimiliano; Brunasso, Lara; Basile, Luigi; Gulì, Carlo; Pino, Maria Angela; Gerardi, Rosa Maria; Messina, Domenico; Umana, Giuseppe Emmanuele; et al. (Frontiers in Oncology, 2022)
Spine is a frequent site of bone metastases, with a 8.5 months median survival time after diagnosis. In most cases treatment is only palliative. Several advanced techniques can ensure a better Quality of Life (QoL) and increase life expectancy. Radiofrequency ablation (RFA) uses alternating current to produce local heating and necrosis of the spinal lesion, preserving the healthy bone. RFA is supported by vertebral reinforcement through kyphoplasty and vertebroplasty in order to stabilize the fracture with polymethylmethacrylate (PMMA) injection, restoring vertebral body height and reducing the weakness of healthy bone. The aim of this study is to demonstrate the efficacy and advantages of RFA plus vertebral reinforcement through PMMA vertebroplasty and fixation in patients affected by bone spinal metastases. We retrospectively analyzed 54 patients with thoraco-lumbar metastatic vertebral fractures admitted to our Unit between January 2014 and June 2020. Each patient underwent RFA followed by PMMA vertebroplasty and transpedicle fixation. We evaluated pain relief through the Visual Analogue Scale (VAS) Score and PMMA vertebral filling based on the mean Saliou filling score. Analysis of variance (ANOVA) was used to test pain relief with statistical significance for p<0.05. A total of 54 patients (median age 63,44 years; range 34-86 years), with a total of 63 infiltrated vertebrae, were treated with RFA, PMMA vertebroplasty and transpedicular screw fixation; average operative time was 60.4 min (range 51–72). The preoperative average VAS score decreased significantly from 7.81 to 2.50 (p < 0.05) after 12 months. Based on Saliou filling score, filling was satisfactory (12–18) in 20 vertebrae (31,7%), mediocre (6–11) in 33 vertebrae (52,4%), inadequate (0–5) in 10 vertebrae (15,9%). A consistent PMMA filling of vertebral bodies was successfully achieved with significant pain relief. Concomitant RFA, PMMA vertebroplasty and pedicle screw fixation represent a safe and effective technique for the management of spinal metastases, improving clinical outcome and pain control.